Dynamics of Infections and Number of Vaccines Needed to Avoid Covid-19 in Europe - Isea, Raúl; Mayo-Garcia, Rafael (International Journal of Coronaviruses, 2020)
The work analyzes the dynamics of transmission of infections by the new coronavirus in twelve European countries, including France, Germany, Italy, Spain, UK, Austria, Croatia, Denmark, Greece, Romania, Czech Republic, and Portugal, whose data from contagion were obtained by Johns Hopkins University until September 24, 2020. The study confirmed that this new coronavirus (SARS-CoV-2) surprised all the countries of the world that had to improve their public health policies to confront this disease according to the results obtained from the calculation of the mantissa. Although the countries were able to improve their policies after the first wave of contagion, Spain and France have the highest proportion of cases that stand out significantly with the rest of the countries in the second wave of infections that the world faces again. Likewise, the beginning of the epidemic outbreak was determined, which could help to track the spread of the disease through European countries (not the first case registered in each country), from which it can be inferred that the outbreak begins in Italy and later the rebound begins in Germany, France, and Spain. Within days, it significantly affects Greece and Austria, reaching Denmark, the Czech Republic, Romania, and Croatia. Finally, the number of people who must be vaccinated to counteract the advance of Covid-19 in these European countries was determined based on the calculation of the Effective Reproductive Number, Rt. The number of people that would have to be vaccinated in all these countries to counteract this disease sums up to 206.830.361.
Keywords: Covid-19; Europe; Mantissa; Epidemic waves; Vaccination; Rt.